Soil polycyclic aromatic hydrocarbons in energy chemical industrial plants of Northwest China: Sources and health risk implications from a field‐based study - Mengcheng Wu; YunZhou Tan; Guodong Kang; Ping Wu; Mengjiao Li; Liangliang Liu; Ning Wang; Ling Wang; Shenghu Zhang; Leilei Lu (Journal of Environmental Quality, 2026)
Abstract Polycyclic aromatic hydrocarbons (PAHs) in soils of energy chemical industrial plants pose considerable ecological and health risks. However, comprehensive studies between petrochemical and coal chemical plants in arid Northwest China remain limited. In this study, 75 surface soil samples (0–20 cm) were collected from 15 large‐scale plants (four petrochemical and 11 coal chemical plants) across the region. Sixteen priority PAHs (∑PAHs) were quantified, and source apportionment was conducted using diagnostic ratios and principal component analysis‐multiple linear regression (PCA‐MLR). In addition, health risks were evaluated using toxic equivalence factors and incremental lifetime cancer risk (ILCR) models. Results showed a stark contrast in PAHs concentrations, with coal chemical plants averaging 4652.2 ng/g and reaching up to 188,506.0 ng/g at a coal tar processing site, compared to 225.6 ng/g in petrochemical plants. Four‐ring PAHs were predominant, accounting for 64.5% and 52.1% of total PAHs in coal chemical and petrochemical soils, respectively, indicative of high‐temperature combustion sources. PCA‐MLR analysis identified coal combustion as the dominant source at coal chemical sites (96.5%), while petrochemical sites exhibited mixed sources, including oil leakage (49.6%) and vehicular emissions (25.6%). Health risk assessment revealed that ILCR values exceeded the US EPA threshold of 10 −6 at seven sampling points in coal chemical plants, with the highest risk observed at site BXT‐2 (1.99 × 10 −4 ), primarily driven by dermal and oral exposure to benzo[a]pyrene. These findings highlight the urgent need for stricter control of high‐temperature industrial processes and improved management of hazardous waste in energy chemical industrial plants.